1994
DOI: 10.1007/bf02986536
|View full text |Cite
|
Sign up to set email alerts
|

A wind tunnel for measuring the gaseous losses of environmental chemicals from the soil/plant system under field-like conditions

Abstract: Volatilization from treated areas is a major source of pesticide residues in air, fog, and rain. This may lead to long-range transport of pesticide residues to remote areas. Up to now most information on pesticide volatilization has come from laboratory experiments under controlled conditions. A new system has been designed and developed to measure the volatile losses of(14)C-labelled chemicals after application; the method compares with agricultural practice of treating soils or plants grown in lysimeters. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 53 publications
1
43
0
Order By: Relevance
“…For a better evaluation of pesticide leaching it is however essential to have knowledge about the factors that govern the leaching process like volatilization, degradation and mineralization. New lysimeter test systems (Stork et al 1994(Stork et al , 1997Schroll and Kühn 2004) take this into account and enable the measurement of pesticide volatilization and mineralization from lysimeter surfaces. These test systems also allow the establishment of a mass balance by which the different processes can be quantified and evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…For a better evaluation of pesticide leaching it is however essential to have knowledge about the factors that govern the leaching process like volatilization, degradation and mineralization. New lysimeter test systems (Stork et al 1994(Stork et al , 1997Schroll and Kühn 2004) take this into account and enable the measurement of pesticide volatilization and mineralization from lysimeter surfaces. These test systems also allow the establishment of a mass balance by which the different processes can be quantified and evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have been carried out under laboratory and simulated field conditions [39,[42][43][44] to simulate volatilization of pesticides under true field conditions. Similarly, studies have also been carried out under controlled conditions in the field [24,45], Laboratory and field procedures for assessment of the inherent tendency of pesticides to volatilise into the air have also been proposed [46] and compared [47,48], Whilst these types of studies can provide a means of evaluating the effects of various microclimatic parameters they are not easy to carry out, particularly for pesticides with low volatility, and results must be interpreted with care.…”
Section: Commission On Agrochemicals and The Environmentmentioning
confidence: 99%
“…These outdoor experiments permit a comprehensive study of the fate of chemicals in soil, plant and seepage water by determining the remaining 14 Cresidues in the compartments. It has been demonstrated that lysimeters with undisturbed soil monoliths reflect the field situation, referring to topsoil processes and formation of plant residues, with sufficient accuracy (Stork et al 1994;Kubiak et al 1990). But it was shown that, due to 14 C-labeled gaseous losses, it was not possible to achieve a complete 14 C-mass balance for several pesticides in these studies.…”
Section: Introductionmentioning
confidence: 98%
“…In the year 1994 a wind tunnel for measuring the gaseous losses of environmental chemicals from soil/ plant systems under field-like conditions (Stork et al 1994) was presented. This wind tunnel is placed onto lysimeter surfaces and all 14 C-pesticide residues volatilizing and mineralizing from the total plant and soil surfaces can be determined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation